Use of three different marker systems to estimate genetic diversity of Indian elite rice varieties - Davierwala, A.P.; Chowdari, K.V.; Kumar, S.; Reddy, A.P.K.; Ranjekar, P.K.; Gupta, V.S.
Genetic diversity among 42 Indian elite rice varieties, which is important for selection of parents for conventional breeding and hybrid program, was evaluated using three different types of DNA markers and parentage analysis. Random amplified polymorphicDNA (RAPD), inter-simple sequence repeat (ISSR)and sequence tagged microsatellite site (STMS)markers resulted in mean heterozygosity values of 0.429, 0.675 and 0.882 over all loci, respectively, and marker index values of 2.21, 4.05 and 5.49, respectively. The three molecular marker systems together provide wider genome coverage and, therefore, would be a better indicator of the genetic relationships among the 42 elite rice cultivars than those revealed using individual molecular markers. A total of 153 bands (91